High-Throughput Genomic Data Reveal Complex Phylogenetic Relationships in Stylosanthes Sw (Leguminosae) - Oliveira, Maria Alice Silva; Nunes, Tomáz; Dos Santos, Maria Aparecida; Ferreira Gomes, Danyelle; Costa, Iara; Van-Lume, Brena; Marques Da Silva, Sarah S.; Oliveira, Ronaldo Simão; Simon, Marcelo F.; Lima, Gaus S. A.; Gissi, Danilo Soares [UNESP]; Almeida, Cícero Carlos de Souza; et al. (Frontiers, 2021)
Allopolyploidy is widely present across plant lineages. Though estimating the correct phylogenetic relationships and origin of allopolyploids may sometimes become a hard task. In the genus Stylosanthes Sw. (Leguminosae), an important legume crop, allopolyploidy is a key speciation force. This makes difficult adequate species recognition and breeding efforts on the genus. Based on comparative analysis of nine high-throughput sequencing (HTS) samples, including three allopolyploids (S. capitata Vogel cv. “Campo Grande,” S. capitata “RS024” and S. scabra Vogel) and six diploids (S. hamata Taub, S. viscosa (L.) Sw., S. macrocephala M. B. Ferreira and Sousa Costa, S. guianensis (Aubl.) Sw., S. pilosa M. B. Ferreira and Sousa Costa and S. seabrana B. L. Maass & 't Mannetje) we provide a working pipeline to identify organelle and nuclear genome signatures that allowed us to trace the origin and parental genome recognition of allopolyploids. First, organelle genomes were de novo assembled and used to identify maternal genome donors by alignment-based phylogenies and synteny analysis. Second, nuclear-derived reads were subjected to repetitive DNA identification with RepeatExplorer2. Identified repeats were compared based on abundance and presence on diploids in relation to allopolyploids by comparative repeat analysis. Third, reads were extracted and grouped based on the following groups: chloroplast, mitochondrial, satellite DNA, ribosomal DNA, repeat clustered- and total genomic reads. These sets of reads were then subjected to alignment and assembly free phylogenetic analyses and were compared to classical alignment-based phylogenetic methods. Comparative analysis of shared and unique satellite repeats also allowed the tracing of allopolyploid origin in Stylosanthes, especially those with high abundance such as the StyloSat1 in the Scabra complex. This satellite was in situ mapped in the proximal region of the chromosomes and made it possible to identify its previously proposed parents. Hence, with simple genome skimming data we were able to provide evidence for the recognition of parental genomes and understand genome evolution of two Stylosanthes allopolyploids.
Keywords: alignment and assembly free; allopolyploidy; chloroplast; mitochondrion; organelle genome; repetitive DNA; sytlosanthes